Importance performance analysis on tourism development in Liang Ndara tourism village, West Manggarai - Agus Trimandala; Dewa Kiskenda; Wayan Agung Panca P (Institute of Computer Science (IOCS), 2022)
Tourism development is highly directed at alternative tourism with a sustainable concept. Therefore, the tourism potential of Liang Ndara Village needs to be developed sustainably with the community as the leading actor. Based on this premise, this research aims to analyze the top priorities for tourism development in the Liang Ndara Tourism Village with a variable approach to tourism potential, community participation, and human resources. The research method used interviews, literature study, observation, and questionnaires. The research sample was taken by purposive sampling, with the stakeholders of Liang Ndara Village as the sample. This analysis uses the importance performance analysis method. There are nine indicators of these results: land access; accessibility of information and communication in the form of internet or wifi; accessibility for the elderly and disabled; The existence of management institutions in the village; Management quality (professionalism, transparency, safety assurance, etc.); involvement of local human resources in village management; management support facilities; management guidelines and tourist behavior, as well as crisis and disaster management systems. From these results, the development of the Liang Ndara Tourism Village needs to maximize the indicators that are on top priority